How I Grow: Newborn through Month Two - Millie Ferrer; Keith Gouin (EDIS, 2003)
How I Grow is a series of six newsletters designed to inform and encourage you during your child's first year of life. The newsletters will discuss developmental changes in your baby, as well as highlight important milestones to keep in mind as you care for him. Do not forget that taking care of yourself is very important, too. Your child needs you! A healthy and happy parent will be able to help an infant develop physically, socially, emotionally, and intellectually.  This document is FCS2217, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: August 2003.